MODELLING IMPACTS OF PLANNED DREDGING OF MAJOR AMAZONIAN RIVERS ON THE WILDLIFE AND PEOPLE OF THE FLOODED FOREST OF LORETO, PERU - BODMER, Richard (2018)
Dredging activities are planned for the Amazon hydrovia project and there is limited scientific evidence of how the proposed dredging could affect both biodiversity and the local population. A model matrix was used to evaluate the possible consequences of dredging on wildlife. According to the matrix, aquatic species show decreasing populations when the water level is low and terrestrial species are negatively affected when floods are intensive. The indigenous Cocama population has adapted to the population changes of the wildlife, dedicating itself more to fishing when the populations of game animals decrease. Shallow areas, locally called "malos pasos", are important habitat types for fish and dolphins. According to the matrix presented in this study, the best scenario would be that the dredging activities do not affect the normal water levels; while, the worst scenario would be when there are droughts and intensive floods.